ANALISIS YURIDIS PROSES PEMERIKSAAN NOTARIS OLEH MAJELIS PENGAWAS DAERAH KOTA LANGSA TERHADAP PELANGGARAN PELAKSANAAN JABATAN NOTARIS - SARAH FADHILLA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Dr. T. Keizerina Devi A, SH, CN, MHum3. Notaris Dr. Suprayitno, SH, MKn Notarial authority to make evidence has caused the deeds he draws to be perfectso that it will not decrease/eliminate their authenticity. People should trust a notary;therefore he has to be monitored. Regional Supervisory Council (MPD) is established bythe Minister to supervise a notary in doing his job in the first phase. There are someviolations against UUJN and KEN done by some of the notaries at Langsa; therefore, theMPD of Langsa plays an important role in decreasing the number of violations. Theresearch problems are how about the regulation on the process of examining notaries byMPD toward their violations, how about the practice of examining them, and how aboutthe procedure of MPD in recommending sanction for MPW on notaries who violateagainst their job.The result of the research shows that the regulation on the process of examininga notary by MPD is stipulated in UUJN, Permenkumham No. M.02.PR.08.10/2004,Permenkumham No. 40/2015, and Kepmenkumham No. M.39-PW.07.10/2004. Inpractice, MPD of Langsa examines and supervises notaries by visiting their offices orwaiting for their regular report. It is found that there are 4 (four) violations having beenexamined by MPD of Langsa in the period of 2015-2018. MPD of Langsa makes a reportregularly and incidentally to MPW of Aceh Province about what has happened in thefield, along with recommendation for sanction on notaries who have violated againsttheir job. The conclusion is that there are many regulations on examining a notary. MPDof Langsa has examined and supervised notaries even though they are not maximal. Itsalso reports about what has happened in the field, along with recommendation ofsanction on notaries who have violated their job. It is recommended that the Governmentestablish independent MPD. MPD of Langsa should develop and supervise regularly anddirectly. It should also be objective in giving recommendation about sanction imposed onnotaries.Keywords: Regional Supervisory Council, Violation against Job Implementation,Examining Notary